Efficacy and safety of spironolactone in moderate to severe acne in females - Sanai, Madiha; Shaukat, Shehla; Ghias, Ayesha; Asghar, Aneela; Nadeem, Muhammad; Ahmad, Tahir Jamil (Journal of Pakistan Association of Dermatologists, 2019)
Background Acne vulgaris is one of the commonest, chronic conditions of skin. Its estimated mean prevalence in Asian women is 30%. Androgens have a key role in the development of this disease so hormonal therapy like spironolactone is an innovative approach in the treatment of acne with successful results. Â Objective To determine the efficacy and safety of spironolactone in moderate to severe acne in females. Â Material and Methods In this longitudinal interventional study, 50 unmarried females of 18 to 45 years, suffering from moderate to severe acne according to Acne Grading Scale of American Academy of Dermatology, presenting to the outpatient of Dermatology Department Unit-II, KEMU/ Mayo Hospital, Lahore, with or without raised testosterone levels were enrolled. Pre-treatment, lesions were counted and Acne Severity Index (ASI) was also calculated. Oral spironolactone 100mg/ day was given for 3 months. Monthly follow-up was done during treatment and for another three months after treatment. Serum testosterone and serum potassium levels were done at baseline, 3rd month and at 6th month. During follow-up visits, ASI and blood pressure were recorded. Photographs were taken at baseline and at every follow-up visit. Percentage reduction of ASI was calculated at the end of therapy. Â Results 50 patients completed the study with mean age of 21 years. Spironolactone was well tolerated and proved efficacious in 94% of cases (p-value â‰¤ 0.001). ASI score at the end of study showed 73% improvement (p-value â‰¤ 0.001) with decrease in the severity of acne after treatment. Patients experienced different side effects during the treatment. Maximum number of patients who had menstrual irregularities was 12, postural hypotension in 4, hyperkalaemia in 2 patients, 2 had polyuria and 8 had other side effects such as headache, weakness and vertigo. All the side effects recovered significantly at the completion of study (p-value Ë‚ 0.001). Â Conclusion Spironolactone is effective and safe medication for females with moderate to severe acne. Â